1958
DOI: 10.1126/science.127.3307.1176
|View full text |Cite
|
Sign up to set email alerts
|

A New Phospholipid, Malignolipin, in Human Malignant Tumors

Abstract: stimulation at a series of points along the floor of the hypothalamus and telencephalon. Twelve points were selected, in 12 different animals. After implantation and a 14-day recovery period, animals were trained to press a lever for chemical stimulation with iproniazid; in this case there was no prior training with electric stimulation.Whereas all animals with ventral hypothalamic pipettes showed a betterthan-chance tendency to press the bar for injection of the chemical, there was a distinct differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1959
1959
1983
1983

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Quick et al prepared bis(tert-butoxycarbonyl)spermidine (26), 58 which proved instrumental in the first total synthesis of codonocarpine.55 Finally Bergeron et al59 have described monobenzylspermidine (27) as a useful precursor for manmade siderophores and other structures in which the different primary amine groups of 27 need not be distinguished. The Chemical Problem-Selectivity Considerations Our own interest in polyamine chemistry originated with the macrocyclic spermidine alkaloids60 celacinnine (32), celabenzine (33), and celafurine (34), whose synthesis appeared to pose a critical test for new lactamization methods.61 A straightforward, unambiguous preparation of acyclic triamino carboxylate salt 30 was accomplished as shown in Scheme II.…”
Section: Previous Synthetic Effortsmentioning
confidence: 99%
“…Quick et al prepared bis(tert-butoxycarbonyl)spermidine (26), 58 which proved instrumental in the first total synthesis of codonocarpine.55 Finally Bergeron et al59 have described monobenzylspermidine (27) as a useful precursor for manmade siderophores and other structures in which the different primary amine groups of 27 need not be distinguished. The Chemical Problem-Selectivity Considerations Our own interest in polyamine chemistry originated with the macrocyclic spermidine alkaloids60 celacinnine (32), celabenzine (33), and celafurine (34), whose synthesis appeared to pose a critical test for new lactamization methods.61 A straightforward, unambiguous preparation of acyclic triamino carboxylate salt 30 was accomplished as shown in Scheme II.…”
Section: Previous Synthetic Effortsmentioning
confidence: 99%
“…Abnormally high amounts o f mucoproteins have also been reported in the blood o f cancer patients or in the perineoplastic tissues, but similar substances also occur in rheumatic disorders and tuberculosis. An increased amount of a specific lipid called malignolipin, has been found in samples of human tumor but these reports by K osaki et al [19] have not been generally confirmed.…”
Section: Biochemical Differences Between Cancer Cells and N Orm Al Cellsmentioning
confidence: 84%
“…A similar genetic failure to degrade one of the gangliosides leads to the storage of this lipid in the ganglion cells, with the resulting syndrome of infantile amaurotic idiocy C5). The recent discovery of a new phospholipid, malignolipin, found only in malignant tumors and never in normal tissues, may, if confirmed, eventually place cancer in this category (6).…”
mentioning
confidence: 94%